The association between ventriculostomy – Related infection and clinical outcomes: A systematic review and meta-analysis. (April 2023) - Chadwick, Simon; Donaldson, Lachlan; Janin, Pierre; Darbar, Archie; Sutherland, Rosie; Flower, Oliver; Hammond, Naomi; Parkinson, Jonathan; Delaney, Anthony
Highlights: The prognosis of patients with ventriculostomy related infection is poorly defined. We found no increase in mortality in patients with ventriculostomy infections. We found no evidence of worse functional neurological outcome. Patients with ventriculostomy infection have increased use of healthcare resources. Abstract: Background: Ventriculostomy – related infection (VRI) is a common complication of patients who require placement of an external ventricular drain (EVD). The clinical outcomes of people who are diagnosed with VRI is poorly characterised. We performed a systematic review and meta-analysis to assess the association between VRI, and clinical outcomes and resource use, in patients treated with an EVD. Methods: We searched MEDLINE, EMBASE, CINAHL and the Cochrane Central Register of clinical trials to identify clinical trial and cohort studies that reported outcomes including mortality, functional outcome, duration of EVD insertion, and intensive care and hospital length of stay. Inclusion criteria and data extraction were conducted in duplicate. Where sufficient data were available, data synthesis was conducted using a random effects model to provide a pooled estimate of the association between VRI and clinical outcomes and resource use. We also pooled data to provide an estimate of the incidence of VRI in this population. Results: Nineteen studies including 38, 247 patients were included in the meta-analysis. There were twelve different definitions of VRI in the included studies. The pooled estimate of the incidence of VRI was 11 % (95 % confidence interval (CI), 9 % to 14 %). A diagnosis of VRI was not associated with an increase in the estimated odds ratio (OR) for mortality (OR 1.07, 95 % CI 0.59 to 1.92, p = 0.83 I 2  = 83.5 %), nor was a diagnosis of VRI associated with changes in neurological outcome (OR 1.42, 95 % CI 0.36 to 5.56, p = 0.89, I 2  = 0.3 %). Those diagnosed with VRI had longer intensive care unit length of stay (estimated pooled mean difference 8.4 days 95 % CI 3.4 to 13.4 days, p = 0.0009, I 2  = 78.7 %) an increase in hospital length of stay (estimated mean difference 16.4 days. 95 % CI 11.6 to 21.2 days, p < 0.0005, I 2  = 76.6 %), a prolonged duration of EVD placement (mean difference 5.24 days, 95 % CI 3.05 to 7.43, I 2  = 78.2 %, p < 0.01), and an increased requirement for an internal ventricular shunt (OR 1.80, 95 % CI 1.32 to 2.46, I 2  = 8.92 %, p < 0.01). Conclusions: Ventriculostomy related infection is not associated with increased mortality or an increased risk of poor neurological outcome, but is associated with prolonged duration of EVD placement, prolonged duration of ICU and hospital admission, and an increased rate of internal ventricular shunt placement.